2010
DOI: 10.1136/gut.2010.222893
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in patients with inflammatory bowel disease treated with thiopurines: cohort from the CESAME Study

Abstract: The results obtained from this cohort indicate that thiopurine use during pregnancy is not associated with increased risks, including congenital abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(101 citation statements)
references
References 24 publications
5
88
1
6
Order By: Relevance
“…Consequently some, caution is warranted with the use of these drugs. Despite limitations of these studies e.g., relatively small sample sizes, or failure to consider the disease activity of IBD, these data are consistent with very moderate thiopurine use as potentially safe during pregnancy [56,57,117] .…”
Section: -Mp/azasupporting
confidence: 55%
See 3 more Smart Citations
“…Consequently some, caution is warranted with the use of these drugs. Despite limitations of these studies e.g., relatively small sample sizes, or failure to consider the disease activity of IBD, these data are consistent with very moderate thiopurine use as potentially safe during pregnancy [56,57,117] .…”
Section: -Mp/azasupporting
confidence: 55%
“…The PIANO registry as of 2012 studied 291 patients exposed to biologic therapy alone and 75 patients exposed to biologics and immunomodulators [117] , and found no increase in congenital abnormalities, infections, or developmental delays which could be clearly attributed to these drugs. Interestingly in the combination group, when CZP was left out of the analysis and only INF and ADA were analyzed individually, there was an increase in infections in the combination therapy group [117] .…”
Section: Biologicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This group found no statistically significant difference in the rate of major malformations (3.5 vs 3%; OR: 1.17; 95% CI: 0.37-3.69), but exposed infants did have a statistically significant increase in premature birth and low birthweight. A more recent French study of 204 pregnant women with IBD found no association between AZA use and risk of adverse pregnancy outcomes, such as interrupted pregnancies (due to spontaneous or elective abortion), congenital abnormalities, preterm deliveries or low birthweight [86].…”
Section: Reviewmentioning
confidence: 99%